"Reconstituted authoritarianism: Islam, service provision and the state in al-Sisi's Egypt". Issue 1 (2nd January 2023) - Russell, Neil
ABSTRACT: Social service provision by non-state actors is cited as an important factor in maintaining authoritarian regime stability in the Middle East. By facilitating their growth regimes ease the burden on their own shrinking resources and avoid resultant social unrest. But these arrangements are not politically risk free, with Islamic opposition groups able to develop substantial social capital. After the Arab Spring, in which regimes faced mass mobilization, and in some cases, nascent democratization, authoritarian elites adapted and transformed their tactics of control to contain newly mobilized societies. Focusing on the crackdown on Islamic service providers in Egypt since 2013, this article shows when a process of democratic transition is reversed, reviving previous arrangements of non-state service provision is deemed unsustainable due to continued political threat. In response, a model of reconstituted authoritarianism is developed that sees the utilization of the state apparatus to extend "direct" controls over non-state service provision, through four strategies: nationalization, corporatization, extraction, and state building. However, the sustainability of this strategy is tempered by state capacity. The article offers a path to increased understanding of authoritarian adaptation after the Arab Spring, and the role of service provision in maintaining regime stability.